The Ultimate Revenge of Benjamin Netanyahu - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
Nero Caesar, the last Roman emperor of the Claudian dynasty, is particularly known for his cruelty and the insane burning of Rome, while playing the lyre and watching from his palace. In the end, the Senate and part of the Gaul army initiated a rebellion and forced him to flee, and shortly after, at age 30, he committed suicide (68 AD). More than 2000 years later, Benjamin Netanyahu, Prime minister and ‘Nero Caesar’ of Israel, is teaching a unique lesson of how to destroy his country in revenge on his ‘humiliation’ of being accused for corruption. To accomplish his ‘vendetta’, Netanyahu designed a lavish plan to demolish the judicial system that prosecuted him and eradicate his trial. At first, he established a coalition to win the elections by joining his Likud party with the religious parties as well as with two parties of extremist settlers in Judea and Samaria (that exploited his personal distress), promising each of them excessive budgets and high-rank positions in the government. Then he nominated a Likud party companion (Yariv Levin), attorney in profession and obsessive against the Israeli Supreme Court, to be the Minister of Justice. Levin immediately appointed Simcha Rothman, a far-right religious member of the Zionism party, as chair of the Constitution, Law, and Justice Committee, with strong motivation to enact radical changes in the legal system, mostly minimization of the authority of the Supreme Court to control governmental decisions. Importantly, in the lack of Constitution in Israel, a major function of this court is to protect citizens’ rights against an abusing government. In passing a legislative cancellation of the over-ruling authority of the Supreme Court, the door for corrupted nominations and dismissal of Netanyahu’s trial, has been opened. This first legislative step incited enormous demonstrations all over Israel with harsh consequences on the economy, security, and social infrastructure, which after more than nine months did not halt the legal revolution. The next legislative steps are now under process beginning with the replacement of the law ‘gatekeepers’, of the government and the various legislative committees, to enable easy confirmation of any decision. Evidently, this step leads to excretion of Netanyahu’s trial and encourages corruption of Knesset members. While Netanyahu’s intentions are clear, the arising question is what are the reasons of all coalition members to support blindly these steps, while ignoring the damages to Israel.